(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The aim of this research is to define and analyze the characteristics of green education, which represents one of the most significant directions in the modern educational system. The objectives of our study are to reveal the essence and advantages of green education, identify the pedagogical challenges that emerge in the learning process, and explore possible ways to address them. In the comprehensive study of the issues presented within the topic, both general scientific methods – such as logical reasoning – and specific methods – such as analysis and comparison – have been applied. As a result of the research, we have concluded that green education is a unique approach within the educational process. Its goal is to cultivate environmental awareness, responsibility, and a culture of sustainable development. It aims to provide learners not only with theoretical knowledge about nature and the environment but also with values and behaviors that promote environmental protection and the rational use of natural resources. Green education integrates pedagogy, ethics, science, and civic responsibility toward a healthy and sustainable future. This educational approach is interdisciplinary, encompassing multiple subjects and contributing to the development of critical thinking. It also emphasizes direct contact with nature and engagement in environmental initiatives. In essence, green education is not merely a process of knowledge transmission – it is a foundation for value-based and behavioral transformation, fostering the formation of a sustainable society.